Wandering souls : and other stories - Caputo, Philip (Arcade Publishing, 2026)
"Pulitzer Prize-winning author Philip Caputo returns to the heart of the human condition with Wandering Souls, a collection of powerful stories that explore war, love, nature, life, and death." --